(untitled) (Nigerian Journal of Technology, 2015)
Failure analysis of a flight control system proposed for Air Force Institute of Technology (AFIT) Unmanned Aerial Vehicle (UAV) was studied using Markov Analysis (MA). It was perceived that understanding of the number of failure states and the probability of being in those state are of paramount importance in order to ensure safety flight of the UAV. Thus, in this study the number of working states and the probability of being in those states for the proposed UAV flight control system was accessed using Markov Analysis (MA). Specifically, the truncated transition state diagram of the UAV flight control system considered in this study was developed and differential equations associated with the transition state diagram were also generated. Laplace transformation technique was used to solve the differential equations. From the findings of the study, the need for design improvement was established. http://dx.doi.org/10.4314/njt.v35i1.24